Implementation of Quality Education at the Darul Falah Amtsilati Islamic Boarding School - Khubab, Ahmad Idmajul; Jaya, Arim Irsyadullah Albin (INJIES: Journal of Islamic Education Studies, 2024)
Introduction of the education program implemented at PP Darul Falah Amtsilati to improve the quality of educational institutions. The aim of this introduction is to introduce existing programs to the public or other people. This objective is described as field findings in the form of a written narrative which aims to obtain an overview of the implementation and quality improvement at PP Darul Falah Amtsilati. The implementation of this program is carried out through an assessment of the Islamic boarding school itself with quality control from within the Islamic boarding school, adjusting conditions to the existing instrument system. The research results show that the implementation of the education program at PP Darul Falah Amtsilati has been implemented and managed well. The preparation of this program is prioritized based on school quality recommendations. There are obstacles to implementation, namely limited skills and infrastructure. The supporting factors are the support of boarding school supervisors and foundations, good coordination between heads of foundations, communication and concern between foundations.